Molecular insights into NLRP3 inflammasome and miRNA modulation in oral cancer - Mannino, Deborah; D’Ariano, Morena; Bello, Ivana; Paterniti, Irene; Casili, Giovanna; Panza, Elisabetta (Frontiers in Pharmacology, 2026)
The NLRP3 inflammasome, a cytosolic multiprotein complex composed of NLRP3, ASC, and caspase-1, orchestrates the maturation of interleukin-1β (IL-1β) and interleukin-18 (IL-18) and the induction of pyroptosis, acting as a central mediator of innate immunity. Although physiologically protective, aberrant NLRP3 activation has been increasingly implicated in tumorigenesis. In oral squamous cell carcinoma (OSCC), current evidence points to a predominantly pro-tumorigenic role, with elevated NLRP3 expression correlating with tumor progression, lymph node metastasis, advanced pathological stage, and reduced survival. Functional studies demonstrate that genetic silencing or pharmacological inhibition of NLRP3 enhances apoptosis and reduces tumor burden. An additional regulatory layer is provided by microRNAs (miRNAs), which fine-tune NLRP3 expression at the post-transcriptional level. Since the identification of miR-223-3p as the first miRNA to directly target NLRP3, several miRNAs, including miR-22-3p, miR-7-5p, and miR-30e-5p, have been shown to suppress NLRP3 activity in various pathological settings, including oral squamous cell carcinoma, where miR-22-3p downregulates NLRP3, inhibiting its proliferation, migration, and invasion. Therefore, the NLRP3 inflammasome represents a key player in cancer development, and its regulation by miRNAs highlights its importance and clinical potential. This review summarizes mechanistic and clinical knowledge on the biology of NLRP3, highlights its dual role in cancer hallmarks, and discusses the therapeutic promise of targeting the NLRP3-miRNA axis in the management of oral cancer.